Sound Cultures in the Medieval North: Tuning in - Eriksen, Stefka G. (Collegium Medievale, 2024)
The aim of this article is twofold: it reviews and collates recent discussions on sound in medieval and Old Norse studies, and in this way, it serves as a historiographical and thematic introduction to the articles of this special issue. The article is bipartite: first, it accounts for studies of intradiegetic sounds, including various categories of human and animal voices and sounds produced by things, animals, nature, and supernatural agencies, as discussed in scholarship focusing on medieval texts. Second, it reviews discussions of extradiegetic sounds, based on material sources, such as the manuscripts themselves, archaeology, architecture, and landscapes. These investigations testify that sound does matter when studying medieval textual and material culture and they legitimate the further investigations of the topic in this special issue, whose main contribution is its focus on sound cultures of the medieval North.